CHARACTERISTIC ANALYSIS OF CHEMICAL COMPOSITION OF MEAT AND FLOUR FROM GONGGONG SNAIL (Strombus canarium) - Winona Oktania Abriestina; Mery Sukmiwati; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTGonggong snail (Strombus canarium), one of fishery commodities from Riau Islands,  has potential and high economic value. Snails, high demand for fishery product, have high nutritional value. This study was aimed to determine the chemical characteristics of meat and flour from gonggong snails (Strombus canarium). The research method consisted of 2 stages: 1) Preparation and chemical analysis of flour snails. The measured parameters included the proportion of the body parts and the chemical analysis of meat snails. Furthermore, the flour snail has analyzed yield and the chemical (moisture, ash, fat and protein content). The results showed that the meat of gonggong snails had a proportion of body parts of 24.05% and the chemical composition of 76.05% moisture(wb), 10.05% ash (db), 8.28 % fat (db) and 78.76% protein (db). Flour snail had a yield of 87.91% and the chemical composition of  (9.18% moisture), (13.52% ash), (5.60% fat) and (77.35% protein). Keyword: Chemical composition, Flour, Gonggong snail, Yield